Pentingnya Pengetahuan tentang Rekrutmen Polisi: Studi Kasus SMAN 3 Kota Sukabumi - Hesri Mintawati; Jhoni Albert (LITERATUS, 2023)
The involvement of human resources (HR) is key to company operations. Human resources play an important role from family to community scale. HR management aims to maximize HR capabilities to achieve the organization's vision. HR management components include planning, recruiting, development, and others. Recruitment techniques can be grouped into formal and informal categories. The National Police is responsible for maintaining national security and ensuring the optimization of its human resources. The National Police's mission includes optimizing resources with the principles of transparency and modernization. This study uses a qualitative approach with descriptive techniques. Primary data was obtained through interviews and observation, while secondary data was obtained through documentation studies. The research location is SMA 3, Sukabumi City, with a focus on recruitment procedures for Polri members. Recruitment and selection play a vital role in ensuring the right individuals are placed in the right positions. Police recruitment criteria must be met by each candidate. The selection process includes health examinations, psychology, academic tests, and physical tests. The quota determined by the National Police Headquarters makes the selection of candidates competitive. The existence of difficulties in assessing candidates demands a better assessment system. The BETAH principle emphasizes quality and transparent recruitment. This research highlights the need for information about national police recruitment for students at SMAN 3, Sukabumi City. The workshops held presented information through various delivery techniques.